ANALISIS KEPATUHAN BEROBAT PENDERITA TB-Paru DI PUSKESMAS SUKAJADI KABUPATEN BANYUASIN SUMATERA SELATAN - Yunita Theresiana (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2020)
Pulmonary Tuberculosis is a chronic infectious disease which still seriously problem that found in the world including Indonesia. Compliance Treatment of Pulmonary Tuberculosis Patients are importantt factor in the success of a treatment. Compliance Treatment of Pulmonary Tuberculosis Patients problems influenced by a lot of factors, that is drugs, health system, environment, economy social dan patient factors.This study used method of cross sectional study to see relation btween the attitudes, income, the role of a treatment supporter, drugs side effects and family support with compliance of taking medicine the lung tuberculosis patients. The sample size are all pulmonary Tb patients with BTA (+) who have been drugs tuberculosis from Sukajadi Public Health Center (PHC) of Banyuasin District Sumatera Selatan Province totaling 61 respondents. Among 61 of respondents there was 90,2% of respondents that did take the medicine regularly. Statistic result showed that there are no significant differentiation between the attitudes (p value=0,535), income (p value=1,000), the role of a treatment supporter (p value=0,189), side effects of drugs (p value=0,128) and there is significant differentiation between family support (p value=0,025) with the compliance treatment of pulmonary tuberculosis patients. Multivariate result showed that family support is the most dominant variable OR = 8,911. Suggested Public Helath Center to be more active sosializing in the education of pulmonary TB disease to pulmonary TB patients and their families that aims to improve compliance with pulmonary TB patients.